Monitoring of white striping and wooden breast cases and impacts on quality of breast meat collected from commercial broilers (Gallus gallus) - Yuwares Malila (2018)
© 2018 by Asian-Australasian Journal of Animal Sciences. Objective: This study aimed at investigating white striping (WS) and wooden breast (WB) cases in breast meat collected from commercial broilers. Methods: A total of 183 breast samples were collected from male Ross 308 broilers slaughtered at the age of 6 weeks (n = 100) and 7 weeks (n = 83). The breasts were subjected to meat defect inspection, meat quality determination and histology evaluation. Results: Of 183, 4 breasts from 6-week-old broilers were classified as non-defective while the others exhibited the WS lesion. Among the 6-week-old birds, the defective samples from the medium size birds (carcass weight ≤2.5 kg) showed mild to moderate WS degree with no altered meat quality. Some of the breasts from the 6-week-old birds with carcass weight above 2.5 kg exhibited WB in accompanied with the WS condition. Besides of a reduction of protein content, increases in collagen matter and pH values in the defective samples (p<0.05), no other impaired quality indices were detected within this group. All 7-week-old broilers yielded carcasses weighing above 2.5 kg and showed abnormal characteristics with progressive severity. The breasts affected with severe WS and WB showed the greatest cook loss, hardness, springiness and chewiness (p<0.05). Development of WB induced significantly increased drip loss in the samples (p<0.05). Histology indicated necrotic events in the defective myofibers. Based on logistic regression, increasing percent breast weight by one unit enhanced the chance of WS and WB development with advanced severity by 50.9% and 61.0%, respectively. Delayed slaughter age from 6 to 7 weeks increased the likelihood of obtaining increased WS severity by 56.3%. Conclusion: Cases of WS and WB defects in Southeast Asia have been revealed. Despite few cases of the severe WS and WB, such abnormal conditions significantly impaired technological properties and nutritional quality of broiler breasts.